Acute zoster Pain and Postherpetic Neuralgia in Thai Patients at Bamrasnaradura Infectiuos Disease Institute - จิระชนากุล, พรชัย (Disease Control Journal, 2010)
The objectives were to study 1. about the pain characteristics and risk factors in Thai patients who developed acute zoster pain and 2. the incidence and risk factors of postherpetic neuralgia. This was prospective observational study in 54 cases of herpes zoster at Bamrasnaradura Infectiuos Disease Institute between June 2007-July 2008. The follow up period was 6 months. It was found that mean age of the cases was 54.9 years. Thirty two cases (59.3%) were immunocompetent status and 22 cases(40.7%) were immunocompromised. In this study we found 8 cases(14.8%) had post herpetic neuralgia and the risk factor was age. Patients who were more than 65 years old had post herpetic pain more than those who were less than 65 years old (p=0.017). And also, this study demonstrated that in case of severe herpes zoster(number of lesions >100), acute zoster pain had developed significantly(p=0.04) compare to mild cases.